A demand chain design for Chinese oatmeal companies - Haitao Wen; Lijing Song (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this paper is to provide a demand chain design framework for Chinese small and medium enterprises in the oatmeal industry, to help them blaze a new trail in China's oatmeal market. Design/methodology/approach: The approach using in the demand chain design is extended Quality Function Development (QFD), which provides a communication tool so that designers can find a way to integrate customers' needs into design chain. Findings: This paper illustrates an investigation of oatmeal consumed in China, and the result shows 9 factors influencing consumer's purchasing decisions mostly. Then use these factors to design the demand chain, and the most important processes and tasks for the enterprises are come out from the fist and the second House of Quality (HOQ), which are the main part of the design. Finally, a demand chain design is completed. Research limitations/implications: It is an application of a demand chain design framework in real Chinese oatmeal market, but the data sample is limited. Consumption surveys should have more data sources with more detailed consumer groups. And the design model needs more real-life examples to verify. Originality/value: A demand chain design framework is presented with being specific to Chinese oatmeal market. It shows a real-life example of demand chain design, and provides the domestic oatmeal companies with an approach to compete in the market.
Keywords: 650; demand chain; design chain; oatmeal